Totally robotic total gastrectomy with D2 lymphadenectomy for gastric cancer via da Vinci Xi platform: Technical details and perioperative outcomes - Chengcai Liang; Jianrong Guo; Guoming Chen; Zhiwei Zhou; Shuqiang Yuan (Intelligent Surgery, 2024)
Background: This study reported the surgical details and outcomes in a case of totally robotic total gastrectomy (TRTG) using the da Vinci Xi robotic system, aiming to share surgical experience in difficult procedures during TRTG and add evidence supporting the feasibility and safety of TRTG. Methods: A 55-year-old male patient diagnosed with adenocarcinoma of gastroesophageal junction underwent TRTG via the da Vinci Xi robotic system in Sun Yat-sen University Cancer Center on January 10, 2024. The surgical details and perioperative outcomes were summarized. Results: With an estimated blood loss of 100 ​ml, the operation lasted 210 ​min, including an anastomosis time of 36 ​min. During a postoperative hospital stay of 7 days, the patient started liquid diet after the removal of gastric tube on the third day. There were no perioperative complications. Postoperative radiography demonstrated no evidence of anastomotic fistulas or luminal narrowing. The final pathology revealed a 4.5∗1.5 ​cm gastric adenocarcinoma with 10/61 positive lymph nodes. The pathological stage of this patient was pT3N3aM0 IIIB. Conclusions: This successful surgery reflected the effectiveness of minimally invasive surgery for total gastrectomy through a totally intracorporeal robotic approach. Future research is warranted to further validate the feasibility and safety of performing TRTG.